Myofacial pain dysfunction syndrome- management protocols revisited - Chaudhary, Akashat; Kumar Dubey, Pavan; Patel, Kavan; R Patel, Jayanti (International Journal of Medical Research and Review, 2016)
Facial pain and its diagnosis have always posed a dilemma for the clinicians. The complex anatomy of the region compounded with the variability of symptoms involved, present a challenging situation during the management of orofacial pain. The dysfunction of these joint results in a large proportion of complaints presented to the dentists. With ever increasing refinements in diagnostic and treatment modalities, dramatic advances have been made in understanding the causes of facial pain related to joint and surrounding musculature. Still the mystery exists regarding the precise diagnosis and treatment of facial pain.